Análise da dinâmica do perfil da população em situação de extrema pobreza no Brasil entre 2012 e 2019 - Azevedo, Lucas Strieder (Universidade Federal do Tocantins, 2022)
The main objective of this work is to investigate the determinant characteristics of the profile of the population living in extreme poverty in Brazil and to analyze the changes that occurred between 2012 and 2019, a period marked by a strong economic recession. Using data from the Pesquisa Nacional por Amostra de Domicílios Contínua, logit regressions were used to demonstrate which profiles suffered the most from the effects of the fall in family income in terms of the chance of living below the extreme poverty line. The results show that younger people, black people, female heads of households, residents of the North and Northeast regions, and people with a lower level of schooling registered an excessive increase in the chances of falling into extreme poverty during the period.